A Cost Analysis of a Stepped Care Treatment Approach for Anxiety Disorders in Youth. Issue 4 (3rd July 2020) - Yeguez, Carlos E.; Page, Timothy F.; Rey, Yasmin; Silverman, Wendy K.; Pettit, Jeremy W.
Abstract : To address the high demand for youth anxiety treatment, researchers have begun to evaluate stepped care approaches to use limited resources efficiently. Quantifying cost savings can inform policy decisions about optimal ways to use limited resources. This study presents a cost analysis of a stepped care treatment approach for anxiety disorders in youth. Youths ( N = 112) completed an 8-session computer-administered attention bias modification treatment (Step 1), and families were given the option to "step up" to cognitive behavioral therapy (CBT; Step 2). Stepped care treatment cost estimates were based on (a) resources used in treatment (i.e., clinician/paraprofessional time, equipment/materials) and (b) Medicaid reimbursement rates for clinician and paraprofessional time. We compared these two cost estimates with a hypothetical standard treatment approach for youth anxiety disorders: CBT only. We also tested predictive models to determine whether they could guide decisions about which youths, based on baseline characteristics, should be assigned to stepped care or directly to CBT only to avoid the costs associated with Step 1. Compared to a hypothetical standard CBT approach, the stepped care treatment was associated with an overall cost savings of 44.4% for the Medicaid reimbursement model and 47.7% for the resource cost model. The predictive models indicated that assigning all youths to stepped care would be more cost-effective than assigning certain youths directly to CBT only. This study provides the first evidence that a stepped care treatment approach for youth anxiety is associated with substantial cost savings compared with a standard CBT.